Mobile Students from Kazakhstan: Migration for Education or Education for Emigration? - Nassimova, Gulnar; Buzurtanova, Marem; Smagulov, Kadyrzhan; Kartashov, Kirill (Studies of Transition States and Societies, 2021)
The article discusses the results of an empirical sociological study on the migratory trajectories of mobile students from Kazakhstan. The study included a series of in-depth interviews and a survey aimed at establishing why they decided to study abroad, how they chose the country to study, and what they were planning to do upon graduation. The ‘push-pull plus’ model was applied to bridge economic and sociological aspects of educational migration from Kazakhstan and to overcome structure-agency dichotomy. Profiles of mobile students across three types of migratory trajectories were developed: Immediate Returnees migrating for educational purposes, i.e. maximisation of utility; Deferred Returnees, whose rational choice is combined with desire and aspiration; and Definite Non-returnees, for whom education is a means of emigration prompted by deprivation due to the situation in the home country, which creates predisposing and proximate drivers.